Application of International Law in Tackling Money Laundering - Trias Pangesti (Westscience Press, 2024)
Money laundering has become a complex and challenging global issue, this complexity is compounded by its cross-border nature, which demands effective international cooperation in its handling and the application of international law to be key to comprehensively combating trafficking and preventing the proliferation of proceeds of crime. International law related to trafficking has evolved rapidly in recent decades. Beginning with the 1988 Vienna Convention on Psychotropic Drugs and Psychotropic Substances, various international legal instruments have been formulated to define trafficking, criminalize its perpetrators, and strengthen cooperation between states. For example the United Nations Convention Against Transnational Organized Crime (Palermo Convention) of 2000 and Recommendation 40 of the FATF, In 2022, the Center for Financial Transaction Reporting and Analysis (PPATK) fully disclosed the amount of Money Laundering (TPPU) which reached IDR 183.88 trillion. Indonesia has ratified various international legal instruments related to TPPU and implemented them in national regulations. Law Number 23 of 2003 concerning Money Laundering and Terrorism Financing is the main legal basis in Indonesia. PPATK, as a UIF (Financial Intelligence Unit), plays an important role in collecting, analyzing, and disseminating information related to TPPU to relevant authorities.